I «Cent noms de Déu» di Ramon Llull. Il Corano e l'epica romanza (Carte Romanze, 2020)
Ramon Llull’s Hundred Names of God has been interpreted, due to its prologue, almost exclusively as an apologetic work against Islam. In this paper, we will demonstrate that this Islamic suggestion has to be considered only as a partial source of this poem, which is aimed mainly to a Christian public and is founded in religious traditions deep-routed in Europe.
Keywords: Ramon Llull; Names of God; Chanson de geste; Qur’ān; Liturgy